Optimalisasi Potensi Bahari di Wilayah 3T: Pendekatan Blue Economy Berbasis Collaborative Governance - Misky, Kias Muhammad Al; Sya'Bany, Raihan Raihan Nabil As; Uswatun; Mawar; Abdul (Kolaborasi : Jurnal Administrasi Publik, 2026)
Kupang Regency, East Nusa Tenggara Province, is a region rich in marine resources, ranging from its beaches to seaweed cultivation, which contributes to local revenue. However, this potential has not yet been supported by good governance from the local government. For example, there are damaged roads, limited access to clean water, poorly maintained beach facilities, and a scarcity of micro, small, and medium-sized enterprises (MSMEs) in the region. This study employs a qualitative method, utilizing data collection and analysis techniques such as interviews, observations, documentation, and literature review. The objective of this study is to analyze the collaborative process in developing blue economy-based coastal tourism across three T-zones in Kupang Regency. According to Kirk Emerson’s theory of collaboration, there are four stages in achieving objectives: collaborative dynamics, collaborative actions, impact, and adaptation. Research findings indicate that although various pentahelix actors have been involved, the collaboration established remains partial, sectoral, and not yet institutionally integrated. Weak inter-institutional coordination, minimal capacity for joint action, and the suboptimal roles of the media and coastal community empowerment are the main obstacles in maritime tourism management. The government’s normative commitment and the abundant potential of marine resources open strategic opportunities to strengthen more effective and sustainable collaborative governance. This study emphasizes that the success of marine tourism development is not only determined by the availability of resources but also heavily depends on the quality of the collaborative process among stakeholders. These findings make an important contribution to enriching the discourse on collaborative governance in the context of coastal regions and can serve as a foundation for formulating inclusive and sustainable marine tourism policies.